PERTUMBUHAN TANAMAN JABON PADA SATU ROTASI (6 TAHUN) DENGAN AWAL TUMPANGSARI PADA HUTAN RAKYAT DI DESA WIDODOMARTANI, KECAMATAN NGEMPLAK, KABUPATEN SLEMAN, YOGYAKARTA - Prijono, Agus; Wahyudiono, Sugeng (Jurnal Wana Tropika, 2021)
One of main supplier on wood industry is Antocephalus cadamba from private forestland. A. cadamba can be harvested at 6 years with the price of Rp 900,000.00 per cubic meter. A. cadamba has been planted in various areas, one of them in Widodomartani, Ngemplak, Sleman, Yogyakarta Province. The succes silviculture A. cadamba if from planting to harvesting with good practice. One of supported succes planting is used multicropping. This research aims to determine the growth at one rotation (six years) with initial planting used multicropping.Planting is done with a distance of 2x2 m in the planting. The growth data (height and diameter) was taken in each treatment (6 treatments) and each treatment tree repeated. The data obtained were analyzed by anova and if there were significant differences in the factors, followed by the LSD test. The analysis showed that the treatment is significantly effect agants height and diameter growth. The growth rate of A. cadamba at 6 years planted is 14,48 m height and 14,61 cm diameter. Key words: Growth, Jabon (Antocephalus cadamba), Initial multicropping